Penerapan Metode Resitasi Untuk Meningkatkan Hasil Belajar PAI Kelas 10 E 1 di SMAN 7 Padang - Jeprianto Jeprianto (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve the learning outcomes of 10th-grade students in class E1 at SMAN 7 Padang by implementing the recitation method in Islamic Education (PAI) learning. The Classroom Action Research (CAR) was conducted over four cycles, each involving planning, implementation, observation, and reflection. The recitation method involved assigning individual and group tasks to encourage students' independence, responsibility, and active participation in learning. The findings revealed significant improvements in students' preparedness and learning outcomes in each cycle. By the fourth cycle, 90% of students demonstrated enhanced material comprehension and active participation during the learning process. The recitation method proved effective in increasing learning motivation, student readiness, and learning outcomes, provided that the tasks were appropriately tailored to students' abilities and regularly evaluated. The main obstacles were students' varied backgrounds and the lack of involvement of some students in completing assignments.